(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article describes a method of working with text on specialty at the sentence level. Two ways of the sentence analysis are suggested – «from the form – to the meaning» and «from the meaning – to the form». The first direction is understanding of the sentence meaning through a model. Depending on the communicative task, different meaningspeech situations are created in the scientific text, which are expressed by certain structural and semantic models. The second way – «from meaning» – is identification of the sentence semantic content with the help of question. The author suggests the following method of work: to find subject and predicate in the sentence; to determine what part of speech expresses the predicate; to formulate a grammatical question to the main word of the combination, which is after the predicate; to write the question down; moving in the opposite direction, to fix the predicate in the question; to fix the subject; to write the question completely and give a brief answer to the question, which will be a semantic center of the sentence.